2013
DOI: 10.1002/prs.11571
|View full text |Cite
|
Sign up to set email alerts
|

Challenges with the use of CFD for major accident dispersion modeling

Abstract: In order to quantify the damage caused by undesired events involving leakages of flammable materials, specific models are used to analyze the spills or jets of gas and liquid, gas dispersion, explosions and fires. The main step of this analysis is to estimate the concentration, in space and time, of the vapor cloud of hazardous substances released into the atmosphere; the purpose is to determine the area where a fire or explosion might occur and the quantity of flammable material in that area. Recently with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Although CFD tools have proven promising to perform analyzes of consequences in environments with complex geometry, there are still challenges to be overcome, as shown by Plasmans et al [6]; previous studies have shown that large differences may arise between the results when working with different tools and/or different CFD analysts to assess the same scenario. The simulation results can be very sensitive to the wide range of computational parameters that must be set by the user; for a typical simulation, the user needs to select the variables of interest, turbulence models, computational domain, computational mesh, boundary conditions, methods of discretization and convergence criteria among others.…”
Section: Omae2014-24587mentioning
confidence: 99%
“…Although CFD tools have proven promising to perform analyzes of consequences in environments with complex geometry, there are still challenges to be overcome, as shown by Plasmans et al [6]; previous studies have shown that large differences may arise between the results when working with different tools and/or different CFD analysts to assess the same scenario. The simulation results can be very sensitive to the wide range of computational parameters that must be set by the user; for a typical simulation, the user needs to select the variables of interest, turbulence models, computational domain, computational mesh, boundary conditions, methods of discretization and convergence criteria among others.…”
Section: Omae2014-24587mentioning
confidence: 99%
“…Nevertheless, as reported by Plasmans et al (2012), previous studies have shown that consequences analysis using CFD are frequently not easily reproduced and, in many occasions, large differences can arise between the simulation results when working with different tools and/or different CFD analysts to assess the same scenario. These problems stem from the fact that the simulation results can be very sensitive to the wide range of computational parameters that must be set by the user; for a typical simulation, the user needs to select the variables of interest, turbulence models, computational domain, computational mesh, methods of discretization, convergence criteria and boundary conditions among others.…”
Section: Introductionmentioning
confidence: 99%
“…CFD tools have proven to be promising to perform consequences analysis in environments with complex geometry (Hanlin, 2006); however, there are still challenges to overcome. As shown by Plasmans et al (2012), previous studies have showed that large differences may arise between the results when different tools and different CFD analysts to assess the same scenario are considered. The results of CDF simulations can be very sensitive to the wide range of computational parameters that must be set by the analyst (Plasmans et al, 2012); for a typical simulation, the user needs to select the variables of interest, the turbulence models to be used, the computational domain and mesh, the boundary conditions, the discretization methods and convergence criteria among others.…”
Section: Main Outcomes Of the Literature Surveymentioning
confidence: 99%
“…As shown by Plasmans et al (2012), previous studies have showed that large differences may arise between the results when different tools and different CFD analysts to assess the same scenario are considered. The results of CDF simulations can be very sensitive to the wide range of computational parameters that must be set by the analyst (Plasmans et al, 2012); for a typical simulation, the user needs to select the variables of interest, the turbulence models to be used, the computational domain and mesh, the boundary conditions, the discretization methods and convergence criteria among others. During the last decades, sensitivity tests, verification and validation studies have been conducted to verify the influence of these parameters in computational simulations (Duijm et al, 1996;Ivings et al, 2007;Coldrick et al, 2009), but clear guidelines of how to appropriately set all these parameters to perform a reliable consequence analysis using CFD are still missing.…”
Section: Main Outcomes Of the Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation